Metal Selectivity of Hevea Protein Isolated from Natural Rubber Latex Skim Serum - Tahir, H.; Misran, M.; R. Othman, M.; N. Ibrahim, N. (International Journal of Engineering and Technology, 2019)
Hevea protein isolated from skim serum, a by-product of centrifugation process, contains useful proteins in extracting metal. It can be used directly from the source or purified before reacting with metal solutions. Those proteins bind with metal at varying degrees. Upon exposure from as low as 2 ppm concentration to up to 20 ppm metal solution concentration, different binding characteristics were seen. The reasons of such inconsistency in the characteristics might be due to the existence of some of the metal itself in the NRL serum. Mg++ and Zn++ are common metal found in NRL products and those metals would show the slightest in binding with hevea protein. Other metals which were covered in this scope of study shows a good binding characteristics disregard of the group of metals belongs. Selectivity was measured from the final concentration of metal in percentage. In most cases, lead, copper and cadmium show good interaction with hevea proteins.